Tinjauan Literatur: Peran Flavonoid dalam Ekstrak Daun Tanaman Obat terhadap Aktivitas Antibakteri - Fitriani, Dilla Novita; Perdana, Analekta Tiara (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2024)
The increasing resistance of bacteria to conventional antibiotics has created a need for jatural antibacterial agents. This study aimed to review the role of flavonoids in medicinal plant leaf extract on antibacterial activity. A systematic literature review was conducted using scientific journals published between 2020 and 2025 Inclusion criteria focused on research articles reporting in vitro baterical activity of leaf extracts containing flavonoids. A total of 20 articels were selected and analyzed based on plant species, extract type, test bacteria, extraction metod, and antibacterial activity results. The analysis showed that leaf extract containing flavonoids generally exhibit antibacterial effects agains both Gram Positive and Gram negative bacteria. Effectiveness varies depending on plant species, flavonoid profile, extract concentration, extract method, and solvent polarity. Most extract Gram negative bacteria are more resistant because of their protective outer membrane. Flavonoids activity through multiple mechan, including disrupting bacterial cell membranes, inhibiting protein and nucleic acid synthesis, interfering with peptidoglycan formation, and inhibiting essential enzymes such as DNA gyrase, Flavonoid structural characteristics, such as the number and position of hydroxyl groups, influence their antibacterial potential. Overall, flavonoid rich leaf extracts have significant potential as natural antibacterial agents, offering multitarget mechanisms that can contribute to bacterial infection control strategies and address antibiotic resistance